Tinjauan Mekanisme Kontrak Pengelolaan Lahan Pertanian Berbasis Adat Istiadat Dalam Kajian Fiqh Muamalah (Desa Temu, Kecamatan Kanor, Kabupaten Bojonegoro) - Beny Septyliyan Primada; Irham Zaki (Universitas Airlangga, 2015)
This study aims to identify and explain the suitability of the system or how cooperation cultivation of agricultural land undertaken Muslim farmers in the village of Temu, Kanor, Bojonegoro which has been run for generations by way of cooperation cultivation of agricultural land in Islam or fiqh kaedah muamalah.Results of this study indicate that there are conformity system or way of cooperation cultivation of agricultural land that the farmers in the village Temu (anvil) with kaedah muamalah Islamic fiqh, because it has met the conditions prevailing in harmony and with both sides to contain the principle that there is an element of mutual muamalah willing and mutually their benefits, as well as a custom ('urf) that do not conflict with the texts of the Qur'an and the Hadith, and also does not contain madharat.